Halal Certification and Implications for MSMEs: A Systematic Literature Review - M. Topit Hidayat; Sri Rahma Witta (UIN Sunan Kalijaga Yogyakarta, 2024)
Research Aims: This study explores the role of halal certification in fostering business growth within the Micro, Small, and Medium Enterprises (MSMEs) sector. Addressing a gap in the literature on the impact of halal certification on MSME performance, it examines its influence on competitiveness, profitability, and market expansion. Methodology: The research employs a Systematic Literature Review (SLR) methodology, gathering relevant articles published between 2019 to 2024 from the Google Scholar database. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) model is utilized to guide the collected studies’ identification, selection, and filtration processes. Research Findings: The findings indicate that halal certification significantly supports MSME operations and enhances product continuity. Consumers are more likely to purchase halal-certified MSME products, positively impacting revenue and sales growth. However, price remains a dominant factor in consumer purchasing decisions, even though halal certification is crucial for meeting Muslim consumer standards. Theoretical Contribution: This study contributes to the literature by shifting the focus from large corporations to MSMEs. It emphasizes halal certification’s economic and operational implications, highlighting its role in attracting Muslim consumers, enhancing market confidence, and fostering MSME growth and sustainability in the global halal market. Research Limitation and Implication: The research is limited to Google Scholar studies within a specific timeframe, possibly excluding relevant findings from other sources. It emphasizes the importance of integrating halal certification into MSME strategies to meet sharia standards, enhance market performance, and provide valuable insights for policymakers and halal industry practitioners.